Wear and corrosion properties of mechanically coated 316 stainless Steel-TiC nanocomposites - Hesamoddin Hamedi; Taghi Isfahani (Results in Engineering)
The mechanical coating (MC) method was used to deposit 316 stainless steel (SS316), TiC, and SS 316-TiC nanocomposite coatings on SS 316 substrates using a ball mill machine at milling durations of 1, 2, 5, 10, and 15 h using relatively cheap and abundant raw material. The chemical composition of the SS 316, TiC, and SS 316-xTiC (x = 20, 50, 80 wt%) nanocomposite coatings deposited by the mechanical coating method has been investigated and the hardness values and the wear and corrosion mechanisms were presented. Dense and uniform coatings were obtained using a ball-to-powder weight ratio (BPR) of 20:1 and an MC duration of 5 h. Among the samples, the SS316-20 wt%TiC coating exhibited the best wear and corrosion resistance. The least mean coefficient of friction was 0.3 for the SS316-20 wt%TiC deposited sample while the largest mean coefficient was for the SS316-80 % TiC sample to be 0.76. The SS 316-20 wt% TiC sample had the lowest wear rate where the highest value was for the %100SS 316 sample being 0.36 × 10−6 and 19 × 10−6 (mm3/Nm), respectively. Corrosion tests revealed that the SS316-20%TiC sample had the best corrosion resistance among the composite samples having a corrosion resistance of 4.9358 μm/Y. The corrosion resistance decreased with the increase of TiC whereas the 80 % TiC coating had severe pitting. Cracks and pores present in the non-uniform 100 % TiC coating resulted in lower corrosion resistance compared to the 100 % SS 316 and composite coatings.